Simulink model for outage studies in power transmission system / Mohamad Azlan Md. Kamal - Md. Kamal, Mohamad Azlan (2007)
This thesis presents the simulink model for outage studies in a power transmission system. The study involved the development of simulink model for all necessary components in power system. Consequently, several outages considering line or generator outages were performed on the system, to evaluate the impacts of these events to system stability. In realizing the possible events, an IEEE 9-bus system was utilized as the test specimen. Responses for voltage, current and active and reactive power profiles were monitored with and without line and generator outages